Urinary hypoxia: an intraoperative marker of risk of cardiac surgery-associated acute kidney injury. Issue 12 (14th March 2018) - Zhu, Michael Z L; Martin, Andrew; Cochrane, Andrew D; Smith, Julian A; Thrift, Amanda G; Harrop, Gerard K; Ngo, Jennifer P; Evans, Roger G
ABSTRACT: Background: Acute kidney injury (AKI) is common after cardiac surgery and profoundly affects postoperative mortality and morbidity. There are no validated methods to assess risk of AKI intraoperatively. Methods: We determined the association between postoperative AKI and intraoperative urinary oxygen tension (PO2 ), measured via a fiber optic probe in the tip of the urinary catheter, in 65 patients undergoing high-risk cardiac surgery requiring cardiopulmonary bypass (CPB). AKI was diagnosed by modified Kidney Disease: Improving Global Outcomes criteria. Results: Urinary PO2 fell during the operation, often reaching its nadir during rewarming or after weaning from CPB. Nadir urinary PO2 was lower in the 26 patients who developed AKI (mean ± SD, 8.9 ± 5.6 mmHg) than in the 39 patients who did not (14.9 ± 10.2 mmHg, P = 0.008). Patients who developed AKI had longer periods of urinary PO2 ≤15 and 10 mmHg than patients who did not. Odds of AKI increased when urinary PO2 fell to ≤10 mmHg 3.60 [95% confidence interval (CI) 1.27–10.21] or ≤5 mmHg [3.60 (95% CI 1.04–12.42), P = 0.04] during the operation. When urinary PO2 fell to ≤15 mmHg, for more than or equal to the median duration for all patients (4.8 min/h surgery), the odds of AKI were 4.85 (95% CI 1.64–14.40), P = 0.004. The area under the receiver-operator curve for this parameter alone was 0.69, and was 0.89 when other variables with P ≤ 0.10 in univariable analysis were included in the model. Conclusion: Low urinary PO2 during adult cardiac surgery requiring CPB predicts AKI, so may identify patients in which intervention to improve renal oxygenation might reduce the risk of AKI.